2017
DOI: 10.3390/ijms18040830
|View full text |Cite
|
Sign up to set email alerts
|

Spondyloarthritis: Matrix Metalloproteinasesas Biomarkers of Pathogenesis and Response to Tumor Necrosis Factor (TNF) Inhibitors

Abstract: The term spondyloarthritis (SpA) is used to describe a group of multifactorial chronic inflammatory diseases characterized by a predisposing genetic background and clinical manifestations typically involving the sacroiliac joint. The absence of pathognomonic clinical and/or laboratory findings generally results in a delay in diagnosis and, consequently, in treatment. In addition, 20–40% of SpA patients are non-responders to tumor necrosis factor (TNF) inhibitor therapies. Given these considerations, it is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…142 Similar findings have been also found in PsA, further confirming the potential role of this molecule as a biomarker. 5759 TNFi induce a significant and rapid decrease in serum MMP-3 levels together with a reduction in conventional variables (ESR and BASDAI). 6163 A similar effect was observed after treatment with ustekinumab, although MMP-3 decrease was not associated with clinical variables.…”
Section: Molecules Involved In Bone Homeostasismentioning
confidence: 97%
“…142 Similar findings have been also found in PsA, further confirming the potential role of this molecule as a biomarker. 5759 TNFi induce a significant and rapid decrease in serum MMP-3 levels together with a reduction in conventional variables (ESR and BASDAI). 6163 A similar effect was observed after treatment with ustekinumab, although MMP-3 decrease was not associated with clinical variables.…”
Section: Molecules Involved In Bone Homeostasismentioning
confidence: 97%
“…Spondyloarthritis is a polygenic rheumatic disease characterized by inflammation of the spine and peripheral joints, as well as extra-articular manifestations, such as inflammation in the intestinal tract, eyes, and skin. Spondyloarthritis comprises differently related but phenotypically distinct disorders, such as psoriatic arthritisarthritis related to inflammatory bowel disease; reactive arthritis, a subgroup of juvenile idiopathic arthritis; and ankylosing spondylitis, which is the prototypic and best-studied subtype [2,75,76,77]. RA and SpA are clinically distinct diseases with different etiologies, both are characterized by synovial hyperplasia, elevated synovial expression of many proinflammatory cytokines including TNFα, IL-1β, and IL-6, increased angiogenesis, and eventual joint destruction [24,76,78,79].…”
Section: Spondyloarthritismentioning
confidence: 99%
“…In the Turina et al study [83], MMP3 showed a statistically significant decrease after two weeks of anti-TNF treatment, however, the effects of treatment were modest and less consistent across different subtypes of SpA. The impact of TNF inhibition on MMP3 levels is so far inconclusive with opposing results from different studies [184], raising the question of whether MMP3 can be used as a predictive biomarker for anti-TNF response. Some studies found a good predictive value for either baseline serum levels and/or reduction over time of MMP3 in SpA and PsA patients under anti-TNF [185,186],…”
Section: Protein Biomarkersmentioning
confidence: 98%